1968
DOI: 10.1121/1.1911119
|View full text |Cite
|
Sign up to set email alerts
|

Model for the Nonlinear Characteristics of Cochlear Potentials

Abstract: In an effort to clarify certain ideas about the nonlinear behavior of the cochlea, a simple nonlinear network was studied. The network was constructed to produce peak-clipping distortion similar to that seen in the cochlear microphonic (CM) of the basal turn of the cochlea. The interference between pairs of tones and the growth of combination tones as well as other manifestations of nonlinearity were similar for the ear and for the network. The degree of similarity between the output of the network and CM from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…This model is derived from the transmission line model so as to ignore the fluid coupling and reduce the system scale; it includes saturation feedback to reproduce the amplification, sharp tuning, and compressive nonlinearity. The saturation function has an important role in explaining the mechanics of 2TS [5,9,10]. Furthermore, it has been suggested that active OHC processes [22,23] that include a saturation property generate nonlinear dynamics in cochlear mechanics [8].…”
Section: Simple Oscillator Model Of Cochleamentioning
confidence: 99%
See 3 more Smart Citations
“…This model is derived from the transmission line model so as to ignore the fluid coupling and reduce the system scale; it includes saturation feedback to reproduce the amplification, sharp tuning, and compressive nonlinearity. The saturation function has an important role in explaining the mechanics of 2TS [5,9,10]. Furthermore, it has been suggested that active OHC processes [22,23] that include a saturation property generate nonlinear dynamics in cochlear mechanics [8].…”
Section: Simple Oscillator Model Of Cochleamentioning
confidence: 99%
“…According to Refs. [9,10], suppression occurs via the saturation function. Therefore, in the simple oscillator model, the amount of feedback via the saturation function is reduced by the suppressor tone.…”
Section: Frequency Dependence Of Cochlear 2tsmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated earlier, these general trends are at least qualitatively similar to trends observed in both ANF and BM responses and support the use of DPOAEs to explore temporal aspects of suppression. Attempts to model suppression have found it difficult to simulate the frequency and level dependence asymmetry (e.g., Engebretson and Eldredge, 1968;Pfeiffer, 1970;Kim et al, 1973;Duifhuis, 1975;among others). The most successful models to date include a compressive nonlinearity of the BM, suggesting that the role of the OHCs is to compress the operating range of the cochlea into an optimum range for the IHCs (e.g., Neely and Kim, 1982;Zwicker, 1985;Yates et al, 1989;Geisler et al, 1990;among others).…”
Section: Introductionmentioning
confidence: 99%